A critical examination of the humanitarian visa as a complementary pathway in ameliorating the plight of “climate displaced persons” in Eastern Africa. - Kanyangi, Leah Aoko (Department of Public Law, 2025)
Eastern Africa has grappled with increasing numbers of displaced persons in the past 20 years because of flooding, tropical storms, landslides, and prolonged seasons of drought. Although there is widespread recognition of the impact of climate change on populations in this region, persons displaced across borders due to climate-related disasters still face challenges in finding protection. This is the case because of their unclear legal status under regional and international law as a unique category of refugees, with scholars arguing over their legitimacy in the international humanitarian landscape. In Eastern Africa, regional economic blocs such as the Intergovernmental Authority for Development (IGAD) have recognised the need to safeguard persons fleeing due to climate change-related disasters. This has been attempted using soft law regional policy frameworks to fill the legal vacuum in recognising human mobility because of climate change disasters. Within this afrocentric context, this thesis adopts a systematic qualitative research methodology, utilizing document analysis, policy review, and case studies to explore complementary pathways for climate-displaced persons in Eastern Africa. The study conducts an in-depth examination of key international and regional frameworks, including UN reports, the Global Compacts on Refugees and Migration, UNHCR's Climate Action Reports, and the IPCC Assessment Reports. It assesses regional instruments and policies relevant to climate-induced displacement to provide a comprehensive understanding of existing legal and policy gaps. Through a critical review of these documents and case studies, the research evaluates the effectiveness of current protection mechanisms, if any and identifies potential solutions to enhance the legal status and rights of climate-displaced individuals. In particular, the thesis proposes humanitarian visas as a practical complementary pathway and legally sound approach to addressing protection gaps, offering a structured pathway for displaced persons facing climate-related threats.